2022
DOI: 10.1093/jme/tjac017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Buffalo Turbine and A1 Mist Sprayer for the Areawide Deployment of Larvicide for Mosquito Control in an Urban Residential Setting

Abstract: The control of medically important container-inhabiting mosquitoes is an ongoing challenge for mosquito control operations. Truck-mounted application equipment is a common option for rapid areawide larvicide deployment utilized by mosquito control operations. We tested the effectiveness of two truck-mounted sprayers (A1 Super Duty + Buffalo Turbine CSM3), for the deployment of water-dispersible biopesticides (VectoBac WDG:VectoLex WDG 50:50). Sixty residences within four residential neighborhoods in New Jersey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Ultralow-volume (ULV) ground spray application with truck-mounted sprayers has been used for adult control in preventive actions or during dengue outbreaks. Studies have shown that area-wide ULV applications of larvicides could be an effective method to control used tires in certain urban areas (Lucia et al, 2009;Jacups et al, 2013;Doud et al, 2014;Unlu et al, 2019;Burtis et al, 2022). On the other hand, thermal fogging is a method that generates ultra-fine droplets (1-50μm), driving the particles deep inside tiny cracks, crevices, and pores of surfaces or different types of containers.…”
Section: Product Application and Limitationsmentioning
confidence: 99%
“…Ultralow-volume (ULV) ground spray application with truck-mounted sprayers has been used for adult control in preventive actions or during dengue outbreaks. Studies have shown that area-wide ULV applications of larvicides could be an effective method to control used tires in certain urban areas (Lucia et al, 2009;Jacups et al, 2013;Doud et al, 2014;Unlu et al, 2019;Burtis et al, 2022). On the other hand, thermal fogging is a method that generates ultra-fine droplets (1-50μm), driving the particles deep inside tiny cracks, crevices, and pores of surfaces or different types of containers.…”
Section: Product Application and Limitationsmentioning
confidence: 99%